Strategies for the valorization of soil waste by geopolymer production: An overview. (15th March 2021) - Capasso, Ilaria; Liguori, Barbara; Ferone, Claudio; Caputo, Domenico; Cioffi, Raffaele
Abstract: The management of huge amounts of waste deriving from several anthropogenic activities, such as manufacturing, construction, mining and quarrying, dredging, represents a great contemporary environmental challenge for many countries worldwide. Among the different recycling possibilities, the use of the excavated soils, obtained from operations such as tunneling, excavations, mining, dredging etc., which are generally considered as soil waste, in the production of innovative eco-sustainable building materials represents an interesting alternative to their disposal. In fact, considering especially their chemical composition, low cost and easy availability, soil wastes seem to be the ideal candidates to be used as secondary raw materials for the manufacture of geopolymer-based materials. The paper intends to present a review of the recent scientific literature regarding the use of different types of soil waste to produce geopolymeric binders. Particular attention is focused on mining waste (deriving from various types of mining industries) and dredged sediments coming from marine harbors and natural and artificial water reservoirs, in order to understand and critically discuss the limits of their disposal approach and, at the same time, show perspectives and challenges for possible future research activities in this field. The production of geopolymer-based building components, starting from mining waste and reservoir sediments, is widely discussed thanks to the numerous scientific findings, while the recycling of marine dredged sediments through geopolymerization represents a completely new and innovative trend in research activity, in fact only few related papers were found in literature. It can be strongly stated that geopolymerization can significantly contribute to a sustainable improvement of soil waste management systems. Graphical abstract: Image 1 Highlights: The need to replace cement with more green binders promoted geopolymer production. Chemical-mineralogical features made soil waste suitable as geopolymer precursors. The combination of soil waste with other kinds of waste was an interesting option. Geopolymers synthesis was promising to reduce soil waste environmental impact.